Revision of the bathydemersal fish genus Pycnocraspedum (Ophidiidae; Teleostei), with description of two new species - Schwarzhans, Werner W.; Psomadakis, Peter N.; Nielsen, Jørgen G. (Zootaxa, 2025)
A taxonomic revision of the deep-water ophidiid genus Pycnocraspedum Alcock, 1889 resulted in seven species being recognized, two of which are described as new: P. africanum sp. nov. from East Africa; P. armatum Gosline, 1954 from Hawaii, Japan and south to New Caledonia; P. fulvum Machida, 1984 from Okinawa Trough; P. microlepis (Matsubara, 1943) from off Japan to East China Sea; P. phyllostoma (Parr, 1933) tropical western Atlantic; P. rowleyensis sp. nov. northwestern Australia; P. squamipinne Alcock, 1889 previously thought to be widely distributed from East Africa to New Caledonia appears to be restricted to the Bay of Bengal. In addition, a fossil otolith-based species is recognized from the Early Pliocene of Italy: P. cetonaense (Schwarzhans, 1978). Pycnocraspedum is characterized by the anterior position of the dorsal-fin origin with the first dorsal-fin pterygiophores positioned in front of the first neural spine (except above the first neural spine in one species), 4 to 6 developed gill rakers on the first gill arch, 11 to 14 precaudal vertebrae (mostly 12 to 13), and small, granular teeth resembling sandpaper with no discernable row or other pattern on jaws and palate. A revised key to the species of Pycnocraspedum is provided. Detailed descriptions, including otolith and morphological comparisons as well as geographical distributions are given for each species.